Facial purpuric cellulitis after ear piercing. - Kaddar, K.; Benahmed, L.; Hormi, O.; Zerrouki, N.; Zizi, N. (European Journal of Pediatric Dermatology, 2025)
Ear piercing in infants, a common cultural practice, can lead to local complications, including infections. We report the case of a rare purpuric form of dermohypodermitis in a one-year-old infant following an earlobe piercing. The infant was treated with intravenous antibiotics and local care, resulting in prompt resolution. The case highlights the importance of vigilant care and hygiene during piercing procedures, particularly in young children, to prevent severe complications.